2015
DOI: 10.1104/pp.15.00354
|View full text |Cite
|
Sign up to set email alerts
|

The SLOW GROWTH3 Pentatricopeptide Repeat Protein Is Required for the Splicing of Mitochondrial NADH Dehydrogenase Subunit7 Intron 2 in Arabidopsis

Abstract: Mitochondria play an important role in maintaining metabolic and energy homeostasis in the cell. In plants, impairment in mitochondrial functions usually has detrimental effects on growth and development. To study genes that are important for plant growth, we have isolated a collection of slow growth (slo) mutants in Arabidopsis (Arabidopsis thaliana). One of the slo mutants, slo3, has a significant reduction in mitochondrial complex I activity. The slo3 mutant has a four-nucleotide deletion in At3g61360 that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
84
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(87 citation statements)
references
References 62 publications
(95 reference statements)
3
84
0
Order By: Relevance
“…S4). These very mild alterations could simply represent pleiotropic effects of the loss of complex I, as observed in several other complex I mutants (Haïli et al, 2013;Colas des Francs-Small et al, 2014;Hsieh et al, 2015), and do not support a direct role of MTL1 in the splicing of these introns. Oppositely, the 16-fold decrease of nad7 intron 2 splicing efficiency resulted in a measured 43 reduction in the accumulation level of nad7 mature mRNA ( Fig.…”
Section: The Mtl1 Protein Is Also Essential For Optimal Splicing Of Nmentioning
confidence: 75%
“…S4). These very mild alterations could simply represent pleiotropic effects of the loss of complex I, as observed in several other complex I mutants (Haïli et al, 2013;Colas des Francs-Small et al, 2014;Hsieh et al, 2015), and do not support a direct role of MTL1 in the splicing of these introns. Oppositely, the 16-fold decrease of nad7 intron 2 splicing efficiency resulted in a measured 43 reduction in the accumulation level of nad7 mature mRNA ( Fig.…”
Section: The Mtl1 Protein Is Also Essential For Optimal Splicing Of Nmentioning
confidence: 75%
“…8 We used ethynyl deoxyuridine (EdU) staining to demonstrate that the slo3 mutant has significantly fewer proliferating cells than wild type (WT) in the primary root. 7 Since the modified nucleoside EdU is incorporated during DNA synthesis, those EdU-stained cells may represent dividing cells in the root apical meristem (RAM) during the treatment. Thus, these results suggest that the slow growth of slo3 is due to a reduction in meristem size and a decrease in cell production rate in the primary root.…”
mentioning
confidence: 99%
“…6 Recently, we reported the characterization of another Arabidopsis slo mutant, slo3, which is similar to slo1 in growth phenotypes. 7 The SLO3 gene encodes a PPR protein of the P subfamily that is required for the splicing of nad7 intron 2 in Arabidopsis mitochondria. 7 The respiratory complex I activity is dramatically reduced in slo3, which may be responsible for the slow growth phenotypes of the mutant.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…NAD7 and NAD4, showed dysfunction in Complex I formation (Gutierres et al 1997;Karpova and Newton 1999). Moreover, studies of several pentatricopeptide repeat protein (PPR) mutants have shown that all mitochondrial-encoded subunits are required for the proper assembly of the respiratory chain complexes (Colas des Francs-Small et al 2014;Colas des Francs-Small and Small 2014;Hsieh et al 2015).…”
Section: Discussionmentioning
confidence: 99%